2007
DOI: 10.1007/s11516-007-0003-1
|View full text |Cite
|
Sign up to set email alerts
|

Returns to education in rural China

Abstract: Based on one of the most widely used datasets by foreign-based sociologists, this paper examines the rate of returns to education in rural China. Compared with the previous studies that showed rather low rates in rural areas throughout the 1980s, this study finds a considerably higher rate in 1996. A chief contributor is the rapid non-agricultural development, which creates enormous upward mobility opportunities, particularly for the more educated. Due to the uneven economic development nationwide, the rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Some existing literature estimate that the returns to education for the disabled and nondisabled, people with different type of disabilities [3] [4]. In China, enormous literature exist in the study of the returns to education in recent years, which including urban residents" rate of returns to education [5], rural residents" returns to education [6] [7], as well as returns to education of special groups, such as the floating population in urban and rural areas [8], minority [9]. However, more than 80 million disabilities have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some existing literature estimate that the returns to education for the disabled and nondisabled, people with different type of disabilities [3] [4]. In China, enormous literature exist in the study of the returns to education in recent years, which including urban residents" rate of returns to education [5], rural residents" returns to education [6] [7], as well as returns to education of special groups, such as the floating population in urban and rural areas [8], minority [9]. However, more than 80 million disabilities have not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…A consistent high level of education holds a great significance among government officials and policymakers, as it is one of the main indicators of human capital and human development. The relationship between employment and human capital in the form of educational attainment has been studied by many social scientists and economists, where some of the researchers support the Human Capital Theory in the form of education (Kjelland, 2008 andPatrinos, 2004), while very few do not support it (Li, 2003;Litao, 2007;Xiu and Gunderson, 2013). Many past research studies have also found that increasing economic return and benefits to a high level of educational attainment can explain an important part of the story.…”
Section: Level Of Education and Employmentmentioning
confidence: 99%
“…Liu finds that for Chinese peasants, "hukou" is the real standard to measure their actual status, benefits, etc. [33]. The easiest way to obtain an urban "hukou", however, is to marry a city man to follow their hukou.…”
Section: The Influences On Rural Female Studentsmentioning
confidence: 99%